Efeitos do aumento da complexidade ambiental induzida por atratores artificiais sobre as assembleias de peixes em lagos de água preta do Parque Nacional de Anavilhanas, Rio Negro (Amazonas - Brasil) - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
Studies on the role of artificial reefs and related structures are quite widespread in the marine literature, however knowledge about its effects on the biota of inland waters is still incipient. A study was conducted in lakes National Park Anavilhanas, Manaus / Am, to analyze the effects of increasing heterogeneity through the use of artificial attractors on the fish assemblages and populations of piscivorous in open water habitat. We also tested the influence of the attractors in two fixed levels of environmental complexity and its relationship to biotic and abiotic factors. Samples were taken four lakes using batteries of different sizes of gillnets, in the morning and evening for twenty-four months. The results showed that the artificial attractors exert a strong influence on fish assemblages in dry seasons, the abundance and diversity respond related to this environmental change. The heterogeneity near the attractors not in the abundance and diversity of the assemblages. Analysis of variance with repeated measures indicated significant differences between attractor and control for the number of species and the Berger-Parker dominance, using as response variable numerical abundance and weight. The environmental variables indicated by significant regression on the diversity of piscivores pH, oxygen and temperature. The number of species of piscivores was higher than in control attractors. Cichlid populations occurred only in areas of the attractor and the period of drought.
Keywords: Atratores artificiais; Piscívoros; Comunidade de Peixes - Amazônia; Artificial attractors; Assemblages of fish - Amazon; Piscivorous; RECURSOS PESQUEIROS E ENGENHARIA DE PESCA